Discovery of novel alphacoronaviruses in European rodents and shrews - Tsoleridis, Theocharis; Onianwa, Okechukwu; Horncastle, Emma; Dayman, Emma; Zhu, Miaoran; Danjittrong, Taechasit; Wachtl, Marta; Behnke, Jerzy M.; Chapman, Sarah; Strong, Victoria; Dodds, Phillipa; Tarlinton, Rachael E.; et al. (MDPI, 2016)
Eight hundred and thirteen European rodents and shrews encompassing seven different species were screened for alphacoronaviruses using PCR detection. Novel alphacoronaviruses were detected in the species Rattus norvegicus, Microtus agrestis, Sorex araneus and Myodes glareolus. These, together with the recently described Lucheng virus found in China, form a distinct rodent/shrew-specific clade within the coronavirus phylogeny. Across a highly conserved region of the viral polymerase gene, the new members of this clade were up to 22% dissimilar at the nucleotide level to the previously described Lucheng virus. As such they might represent distinct species of alphacoronaviruses. These data greatly extend our knowledge of wildlife reservoirs of alphacoronaviruses.